MEDIA SOSIAL DALAM PEMILIHAN KEPALA DESA: Studi Kampanye Online dan Peluang Keterpilihan - Permatasari, Septaria; Fitriyah, Fitriyah; Adnan, Muhammad (Jurnal Politik Pemerintahan Dharma Praja, 2022)
This study aims to analyze the use of social media for online campaigns in village head elections (pilkades) and the chances of candidates being elected. Social media, which used to be only a means of entertainment, is now being looked at by politicians as a new space to gain voter support in elections (including the presidential election and local head elections). However, studies for the Pilkades have not been carried out. This study uses a qualitative method with a descriptive approach in the 2020 Padangan Village Pilkades, Padangan District, Bojonegoro Regency. The data used are primary data obtained through in-depth interviews with 12 informants who were selected purposively and through observation, as well as secondary data from pilkades documents. Analysis of the data using the Miles and Huberman analysis model. The results of the study show that social media can be a great opportunity to support village head candidates in gaining popularity and winning in the village head election if a village head candidate can use social media for online campaigns appropriately. Factors that influence the successful use of social media in online campaigns for village head candidates include: First, who is involved in the online campaign. The second is the type of social media. Third, the campaign content presented.